The Influence of Fresh Raffia Palm Trunk on the Bioremediation of Oil-Based Drill - Bright Nweke; Achinike Okogbule Wonodi; Ikenna. M. Chikwue (International Journal of Pollution: Prevention & Control, 2024)
This study determines the effect of fresh raffia palm for biodegradation of oil-based drill cuttings bioremediation. The experiment was conducted at the rivers institute of Agricultural research and training (RIART) located at the Rivers State University, Port Harcourt. Samples of oil-based drill cuttings were bulked in eleven reactors with four replications (T1, T2, T3-T11). The physiochemical properties of the initial drill cuttings were analyzed. Also, the physiochemical properties of the oil- based drill cuttings of fresh raffia palm such as. Total Petroleum Hydrocarbon, Benzene Toluene Ethylene Xylene, Total Polycyclic Aromatic Hydrocarbon were analyzed in the laboratory before and after treatments. Total Petroleum Hydrocarbon, Benzene Toluene Ethylene Xylene and Polycyclic Aromatic Hydrocarbon reduction were drastic in all treatment options at the end of 16weeks of remediation. Total Petroleum Hydrocarbon, Polycyclic Aromatic Hydrocarbon and Benzene Toluene Ethylene Xylene rate of percentage reduction assortments from 84 to 91% in all the treatment options for the period of 16weeks. Results also displayed a high coefficient of determination of (R2) between the range of 0.9809 to 0.9953 in all the treatment option. The results as obtained using the Analysis of Variance (ANOVA) showed a significant difference at 95% and highly significant at 99% confidence level. Similarly, the coefficient of variation of every low percentage were revealed for the treatment option respectively. This confirmed that the experimental Root Mean Square Error (RMSE) was very low, Residual Prediction Deviation (RPD) are considered excellent, thereby it is acceptable and reliable.
Keywords: Fresh Raffia Palm and Oil-based drill cutting; Polycyclic Aromatic; biodegradation; bioremediation